Best practices for supporting researchers’ mental health in emotionally demanding research across academic and non-academic contexts - Mary L. Quinton; Karen L. Shepherd; Jennifer Cumming; Grace Tidmarsh; Maria R. Dauvermann; Sian L. Griffiths; Sally Reynard; Amanda Skeate; Anita Fernandes; Tasneem Choucair; James Downs; Karen Harrison Dening; et al. (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Researcher mental health in emotionally demanding research (EDR) has been recognized as important, but research to date has often been limited to academic research contexts, qualitative research, or single disciplines. The aim of this study was to identify best practices to promote researchers’ mental health in EDR across academic and non-academic contexts. Methods Twenty-six researchers experienced in EDR (aged 33–64) were recruited across sectors and disciplines (e.g. sport psychology, palliative care, conflict resolution). Semi-structured online 2:1 interviews were conducted between October 2023 and January 2024. The co-designed interview guide asked questions on best practices at individual and contextual levels when undertaking EDR. Interviews were analysed through reflexive thematic analysis. Results Three themes were generated: (1) the need for a psychologically informed research culture; (2) actions and principles in the immediate research environment; and (3) researcher boundaries with the research, others, and oneself. Underlying mechanisms across themes included tailored, iterative and flexible, and collaborative. Conclusions A shift is needed towards a more psychologically informed research culture to support mental health in EDR. Findings have implications for research organizations, conference organizers, and funders as greater resources are needed for researchers in EDR, regardless of method, discipline, or sector.